(untitled) (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2025)
Structural deformation monitoring is crucial for ensuring the safety and longevity of infrastructure. Traditional methods, such as total stations and laser scanning, provide high accuracy but often come with high costs and logistical challenges. Close-range photogrammetry (CRP) offers a cost-effective, non-contact alternative for detecting structural deformations with high precision. This study evaluates the effectiveness of CRP for deformation monitoring by conducting 3D reconstructions, accuracy assessments, and comparative analyses with traditional surveying methods.